Mitochondrial Outer Membrane Channels: Emerging Diversity in Transport Processes. (30th April 2018) - Becker, Thomas; Wagner, Richard
Abstract : Mitochondrial function and biogenesis depend on the transport of a large variety of proteins, ions, and metabolites across the two surrounding membranes. While several specific transporters are present in the inner membrane, transport processes across the outer membrane are less understood. Recent studies reveal that the number of outer membrane channels and their transport mechanisms are more diverse than originally thought. Four protein‐conducting channels promote transport of distinct sets of precursor proteins across and into the outer membrane. The voltage‐dependent anion channel (VDAC) forms the major channel for small hydrophilic molecules. In addition, three channels with yet unknown substrate specificity exist in the outer membrane. In this review, we outline the emerging functional diversity, selectivity, and regulation of mitochondrial outer membrane channels. The presence of several channel‐forming proteins challenges the traditional view that the outer membrane forms an unspecific size‐exclusion filter for the flux of small hydrophilic molecules. Abstract : Mitochondrial outer membrane channels transport a large variety of metabolites, ions, and proteins. Recent studies reveal that the number of outer membrane channels is larger than originally thought. Here, the emerging diversity and functional specificity of outer membrane channels is reviewed.